Ultraviolet-curable resin composition, method for producing light-emitting device, light-emitting device, and touch panel

A UV curable resin composition with specific permittivity and viscosity is used to address misalignment issues in inkjet molding, ensuring precise positioning and reducing defects in optical components for touch panels and light emitting devices.

JP7611477B2Active Publication Date: 2025-01-10PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023117084
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-10
Estimated Expiration
2039-10-15

AI Technical Summary

Technical Problem

The issue of misalignment in the positioning of resin droplets during the inkjet method for manufacturing light emitting devices, particularly due to separation or air currents, leading to defects in optical components.

Method used

A UV curable resin composition with a photopolymerizable compound and photopolymerization initiator, having a relative permittivity of 8.0 or less and viscosity of 50mPa·s or less, is used to mold optical components using an inkjet method, ensuring precise positioning and reducing the impact of electric and magnetic fields.

Benefits of technology

The composition allows for accurate molding without positional deviation, reducing defects and improving manufacturing efficiency while maintaining low dielectric constant and heat resistance, suitable for applications in touch panels and light emitting devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611477000030
    Figure 0007611477000030
  • Figure 0007611477000031
    Figure 0007611477000031
  • Figure 0007611477000001
    Figure 0007611477000001
Patent Text Reader

Abstract

To provide an ultraviolet curable resin composition that can be molded by the inkjet technique and ensures droplets reach a consistent position when ejected by the inkjet technique.SOLUTION: An ultraviolet curable resin composition includes a photopolymerizable compound (A) and a photopolymerization initiator (B). The relative permittivity of the photopolymerizable compound (A) at 25°C and a frequency of 10 kHz is 8.0 or less, and the viscosity at 25°C is 50 mPa s or less. The ultraviolet curable resin composition is molded by the inkjet technique (excluding the case where it contains coagulative gas).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ultraviolet-curable resin composition, a method for manufacturing a light-emitting device, a light-emitting device, and a touch panel, and more particularly, to an ultraviolet-curable resin composition containing a photopolymerizable compound and a photopolymerization initiator, a method for manufacturing a light-emitting device using the ultraviolet-curable resin composition, a light-emitting device including an optical component made from the ultraviolet-curable resin composition, and a touch panel including the light-emitting device. [Background technology]

[0002] In a light-emitting device having a light-emitting element such as an organic EL element as a light source, for example, the organic EL element is disposed on a support substrate, a transparent substrate is disposed so as to face the support substrate, and a transparent sealant is filled between the support substrate and the transparent substrate. The sealant is prepared, for example, by an inkjet method.

[0003] For example, Patent Document 1 discloses a sealant for organic electroluminescence display elements, which contains a polymerizable compound and a polymerization initiator, and is characterized in that the viscosity at 25°C is 5 to 50 mPa s, the surface tension at 25°C is 15 to 35 mN / m, and the Poisson's ratio at 25°C of the cured product is 0.28 to 0.40 (see claim 1 in Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 074506 Summary of the Invention [Problem to be solved by the invention]

[0005] When a resin composition is molded by spraying droplets of the resin composition toward a suitable substrate using an inkjet method, the droplets may reach positions on the substrate that are different from the positions designed in the design. Such positional deviation may occur when the sprayed droplets separate before reaching the substrate or when the droplets are carried away by an air current, but even if these factors are eliminated, the droplets may still be misaligned.

[0006] An object of the present invention is to provide an ultraviolet-curable resin composition that can be molded by an inkjet method and that is unlikely to cause deviation in the position where droplets reach when sprayed by the inkjet method, a method for manufacturing a light-emitting device that uses the ultraviolet-curable resin composition, a light-emitting device that includes an optical component made from the ultraviolet-curable resin composition, and a touch panel that includes the light-emitting device. [Means for solving the problem]

[0007] An ultraviolet-curable resin composition according to one embodiment of the present invention contains a photopolymerizable compound (A) and a photopolymerization initiator (B). The photopolymerizable compound (A) has a relative dielectric constant of 8.0 or less at 25° C. and a frequency of 10 kHz, and a viscosity of 50 mPa s or less at 25° C. The ultraviolet-curable resin composition is molded by an inkjet method.

[0008] A method for manufacturing a light-emitting device according to one embodiment of the present invention is a method for manufacturing a light-emitting device including a light source and an optical component that transmits light emitted by the light source, and includes forming the ultraviolet-curable resin composition by an inkjet method to form a coating film, and irradiating the coating film with ultraviolet light to form the optical component.

[0009] A light emitting device according to one aspect of the present invention includes a light source and an optical component that transmits light emitted by the light source, the optical component being made of a cured product of the ultraviolet curable resin composition.

[0010] A touch panel according to an aspect of the present invention includes the light-emitting device and a touch sensor. Effect of the Invention

[0011] According to one aspect of the present invention, there are provided an ultraviolet-curable resin composition that can be molded by an inkjet method and that is unlikely to cause deviation in the position where droplets reach when sprayed by the inkjet method, a method for manufacturing a light-emitting device that uses the ultraviolet-curable resin composition, a light-emitting device that includes optical components made from the ultraviolet-curable resin composition, and a touch panel that includes the light-emitting device. [Brief description of the drawings]

[0012] [Figure 1] Fig. 1A is a schematic cross-sectional view showing a first example of an organic EL light-emitting device according to one embodiment of the present invention, and Fig. 1B is a schematic cross-sectional view showing a second example of the organic EL light-emitting device according to the first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a touch panel according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, one embodiment of the present invention will be described.

[0014] The ultraviolet-curable resin composition according to this embodiment (hereinafter also referred to as composition (X)) contains a photopolymerizable compound (A) and a photopolymerization initiator (B). The photopolymerizable compound (A) has a relative dielectric constant of 8.0 or less at 25°C and a frequency of 10 kHz, and a viscosity of 50 mPa s or less at 25°C. Composition (X) is molded by an inkjet method.

[0015] According to this embodiment, the composition (X) is molded and then cured to produce a cured product. This cured product can be applied to, for example, optical components in a light emitting device 1 that transmit light emitted by a light source (see Figs. 1A and 1B). In this embodiment, since there is no need to heat the composition (X) when curing it, the light source in the light emitting device 1 is less likely to be damaged by heat, particularly when producing optical components in the light emitting device 1.

[0016] In addition, since the viscosity of the photopolymerizable compound (A) at 25°C is 50 mPa·s or less, it is easy to reduce the viscosity of the composition (X). Therefore, the composition (X) can be easily molded by the inkjet method, and therefore the composition (X) can be easily molded with good positional accuracy. In addition, compared to molding by a printing method involving contact such as a screen printing method, when the composition (X) is molded by the inkjet method, foreign matter is less likely to be mixed into the composition (X) and its cured product, and therefore the yield when manufacturing optical parts is less likely to deteriorate.

[0017] Furthermore, in this embodiment, since the photopolymerizable compound (A) has a relative dielectric constant of 8.0 or less at 25°C and a frequency of 10 kHz, the trajectory of the droplets of the composition (X) sprayed by the inkjet method is not easily affected by electric and magnetic fields. Therefore, even if the target to which the composition (X) is applied is charged or magnetized, the trajectory of the droplets is not easily bent or the droplets are not easily repelled by the member due to the interaction between the member and the droplets, and therefore the arrival position of the droplets on the target is not easily shifted from the designed position. Therefore, the composition (X) can be easily molded with even higher positional accuracy, and defects are less likely to occur in optical parts and the like manufactured from the composition (X).

[0018] As a result, in this embodiment, even if a treatment involving charging or magnetizing the component, such as plasma treatment, is performed in advance for the purpose of improving wettability, when molding the composition (X) on a component made of an inorganic material, the composition (X) can be easily molded with good positional accuracy. That is, even if the component is charged or magnetized by the above-mentioned treatment, the trajectory of the droplets of the composition (X) sprayed by the inkjet method is not easily affected by the electric field or magnetic field, so that the droplets are not easily displaced. This can reduce the effort and equipment required for performing treatment such as de-electrifying the component, and can easily increase the efficiency of manufacturing optical components from the composition (X).

[0019] Furthermore, since the photopolymerizable compound (A) has a relative dielectric constant of 8.0 or less at 25°C and a frequency of 10 kHz, it is easy to lower the relative dielectric constant of the cured product of the composition (X) and the optical components. Therefore, the optical components are unlikely to cause malfunctions in the light-emitting device 1. That is, for example, if the display device equipped with optical components is a touch panel, if the relative dielectric constant of the optical components is high, it may affect the sensitivity of the touch panel and cause malfunctions, but in this embodiment, the relative dielectric constant of the optical components can be easily lowered, making it difficult for malfunctions to occur.

[0020] The dielectric constant of the photopolymerizable compound (A) at 25° C. and a frequency of 10 kHz is more preferably 7.5 or less, and even more preferably 7.0 or less. The lower the dielectric constant of the photopolymerizable compound (A), the more preferable, and ideally 0.

[0021] The dielectric constant of the cured product at a temperature of 25°C and a frequency of 100 kHz is preferably 3.0 or less. In this case, malfunction of the light emitting device 1, such as a touch panel, caused by optical components can be particularly prevented. The dielectric constant of the cured product is more preferably 2.8 or less, and particularly preferably 2.7 or less. The lower the dielectric constant of the cured product, the more preferable, and ideally 0.

[0022] It is preferable that the composition (X) does not contain a solvent, or the content of the solvent (percentage of the solvent to the entire composition (X)) is 1 mass % or less. In this case, outgassing due to the solvent is unlikely to occur from the composition (X) and the cured product of the composition (X). Therefore, the viscosity change of the composition (X) due to the evaporation of the solvent is unlikely to occur, and the storage stability of the composition (X) is improved. In addition, it is possible to make it difficult for voids due to outgassing to occur in the light emitting device 1. Therefore, it is difficult for water to reach the light source through the voids, and the light source is unlikely to deteriorate due to water. In addition, it is possible to eliminate the need for a drying process for removing the solvent from the composition (X) and the cured product when manufacturing the optical component. There may be a drying process for removing the solvent from at least one of the composition (X) and the cured product, but in this case, it is possible to reduce at least one of the heating temperature and the heating time in the drying process. Therefore, it is possible to make it difficult for outgassing to occur from the optical component without reducing the manufacturing efficiency of the optical component. Furthermore, if the composition (X) does not contain a solvent or the content of the solvent is 1% by mass or less, when the composition (X) is molded, particularly by an inkjet method, the thickness of the molded composition (X) is unlikely to be reduced due to the evaporation of the solvent, and therefore the thickness of the optical component is unlikely to be reduced. The content of the solvent is more preferably 0.5% by mass or less, even more preferably 0.3% by mass or less, and particularly preferably 0.1% by mass or less. It is particularly preferable that the composition (X) does not contain a solvent or contains only a solvent that is inevitably mixed in.

[0023] The glass transition temperature of the cured product of the composition (X) is preferably 80°C or higher. That is, the composition (X) preferably has a property of curing to become a cured product having a glass transition temperature of 80°C or higher. In this case, the cured product can have good heat resistance. Therefore, for example, when the cured product is subjected to a treatment accompanied by a temperature increase, the cured product is not easily deteriorated. Therefore, for example, when a passivation layer or the like is produced by a deposition method such as a plasma CVD method so as to cover an optical component produced from the composition (X), the optical component is not easily deteriorated even if the optical component is heated. In addition, by increasing the heat resistance, the optical component can be adapted to an in-vehicle application that has strict requirements for heat resistance. The glass transition temperature of the cured product is more preferably 90°C or higher, and even more preferably 100°C or higher. This glass transition temperature of the cured product can be achieved by the composition of the composition (X) described in detail below.

[0024] The viscosity of composition (X) at 25°C is preferably 40 mPa·s or less. In this case, composition (X) can be easily molded by the inkjet method at room temperature. This viscosity is more preferably 30 mPa·s or less, even more preferably 25 mPa·s or less, even more preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. This viscosity is also preferably 1 mPa·s or more, and is also preferably 5 mPa·s or more.

[0025] It is also preferable that the viscosity of the composition (X) at 40°C is 40 mPa·s or less. In this case, no matter what the viscosity of the composition (X) is at room temperature, it is possible to lower the viscosity by slightly heating the composition (X). Therefore, by heating, the composition (X) can be easily molded by the inkjet method. In addition, since the viscosity of the composition (X) can be lowered without significantly heating it, it is possible to prevent the composition of the composition (X) from changing due to the volatilization of the components in the composition (X). It is more preferable that the viscosity is 30 mPa·s or less, even more preferable that the viscosity is 25 mPa·s or less, even more preferable that the viscosity is 20 mPa·s or less, and particularly preferable that the viscosity is 15 mPa·s or less. It is also preferable that the viscosity is 1 mPa·s or more, and it is also preferable that the viscosity is 5 mPa·s or more.

[0026] Such a low viscosity of composition (X) can be achieved by the composition of composition (X) described in detail below.

[0027] The volatility of 20 mg of the composition (X) is preferably 40% or less when the composition (X) is heated at 100°C for 30 minutes using a thermogravimetric analyzer. The volatility of the composition (X) is defined as the percentage of the weight loss of the composition (X) after the treatment (the difference between the weight of the composition (X) before the treatment and the weight of the composition (X) after the treatment) relative to the weight of the composition (X) before the treatment. In this case, the low volatility of the composition (X) can enhance the storage stability of the composition (X). In addition, outgassing is less likely to occur from the cured product of the composition (X) and the optical components. Therefore, voids due to outgassing are further less likely to occur in the light-emitting device 1. The volatility of the composition (X) can be determined by heating 20 mg of the composition (X) at 100°C for 30 minutes using a thermogravimetric analyzer and calculating the weight loss after the treatment relative to the weight before the treatment. When 20 mg of composition (X) is heated at 100° C. for 30 minutes using a thermogravimetric analyzer, the volatility is more preferably 30% or less, and even more preferably 20% or less. The lower limit of the volatility of composition (X) is not particularly limited, but may be, for example, 0.1% or more.

[0028] This embodiment will be described in further detail below.

[0029] 1. Light emitting device First, the structure of the light emitting device 1 will be described when the optical component is a sealant 5 that seals the light emitting element 4, which is a light source in the light emitting device 1. The light emitting device 1 includes a light emitting element 4 and a sealant 5 that covers the light emitting element 4. The sealant 5 may cover the light emitting element 4 in a state of direct contact with the light emitting element 4, or may cover the light emitting element 4 with some layer interposed between the sealant 5 and the light emitting element 4. The light emitting device 1 may be, for example, a lighting device or a display device.

[0030] The light-emitting element 4 includes, for example, a light-emitting diode. The light-emitting diode includes, for example, at least one of an organic EL element (organic light-emitting diode) and a micro light-emitting diode. When the light-emitting element 4 includes an organic light-emitting diode, the light-emitting device 1 including the light-emitting element 4 is, for example, an organic EL display. When the light-emitting element 4 includes a micro light-emitting diode, the light-emitting device 1 including the light-emitting element 4 is, for example, a micro LED display. Note that EL stands for electroluminescence, and LED stands for light-emitting diode.

[0031] A first example of the structure of the light emitting device 1 will be described with reference to Fig. 1. This light emitting device 1 is a top emission type. The light emitting device 1 includes a support substrate 2, a transparent substrate 3 that faces the support substrate 2 with a gap therebetween, a light emitting element 4 on the surface of the support substrate 2 that faces the transparent substrate 3, and a sealant 5 that is filled between the support substrate 2 and the transparent substrate 3. In addition, in the first example, the light emitting device 1 includes a passivation layer 6 that covers the surface of the support substrate 2 that faces the transparent substrate 3 and the light emitting element 4. That is, the passivation layer 6 is interposed between the light emitting element 4 and the sealant 5 that covers the light emitting element 4.

[0032] The support substrate 2 is made of, for example, a resin material, but is not limited thereto. The transparent substrate 3 is made of a material having light-transmitting properties. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. When the light-emitting element 4 includes an organic EL element, the organic EL element includes, for example, a pair of electrodes and an organic light-emitting layer between the electrodes. The organic light-emitting layer includes, for example, a hole injection layer, a hole transport layer, an organic light-emitting layer, and an electron transport layer, and these layers are laminated in the above order. Although only one light-emitting element 4 is shown in FIG. 1, the light-emitting device 1 may include a plurality of light-emitting elements 4, and the plurality of light-emitting elements 4 may form an array on the support substrate 2. The passivation layer 6 is preferably made of silicon nitride or silicon oxide.

[0033] A second example of the structure of the light emitting device 1 will be described with reference to Fig. 2. Elements in Fig. 2 that are common to the first example shown in Fig. 1 are given the same reference numerals as in Fig. 1, and detailed descriptions thereof will be omitted as appropriate. The light emitting device 1 shown in Fig. 2 is also of a top emission type. The light emitting device 1 includes a support substrate 2, a transparent substrate 3 that faces the support substrate 2 with a gap therebetween, a light emitting element 4 on the surface of the support substrate 2 that faces the transparent substrate 3, and a sealant 5 that covers the light emitting element 4.

[0034] When the light-emitting element 4 includes an organic EL element, the organic EL element, like the first example, includes, for example, a pair of electrodes 41, 43 and an organic light-emitting layer 42 between the electrodes 41, 43. The organic light-emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light-emitting layer 423, and an electron transport layer 424, which are laminated in the above order.

[0035] The light emitting device 1 includes a plurality of light emitting elements 4, which form an array 9 (hereinafter referred to as element array 9) on a support substrate 2. The element array 9 also includes a partition 7. The partition 7 is located on the support substrate 2 and separates two adjacent light emitting elements 4. The partition 7 is produced, for example, by forming a photosensitive resin material using a photolithography method. The element array 9 also includes connection wiring 8 that electrically connects the electrodes 43 and the electron transport layers 424 of adjacent light emitting elements 4 to each other. The connection wiring 8 is provided on the partition 7.

[0036] The light emitting device 1 also includes a passivation layer 6 covering the light emitting element 4. The passivation layer 6 is preferably made of silicon nitride or silicon oxide. The passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the element array 9 in a state where the first passivation layer 61 is in direct contact with the element array 9, thereby covering the light emitting element 4. The second passivation layer 62 is disposed on the opposite side of the element array 9 with respect to the first passivation layer 61, and a gap is provided between the second passivation layer 62 and the first passivation layer 61. The sealant 5 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is interposed between the light emitting element 4 and the sealant 5 covering the light emitting element 4.

[0037] Furthermore, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. The material of the second sealing material 52 is not particularly limited. The material of the second sealing material 52 may be the same as or different from the sealing material 5.

[0038] A method for producing an optical component using the composition (X) and a method for producing the light emitting device 1 will be described.

[0039] In this embodiment, it is preferable to form a coating film by forming the composition (X) by the inkjet method, irradiate the coating film with the composition (X) by ultraviolet light, and then heat the composition to form an optical component. In this embodiment, the composition (X) can be applied and formed by the inkjet method.

[0040] When applying composition (X) by the inkjet method, if composition (X) has a sufficiently low viscosity at room temperature, composition (X) can be molded by applying it by the inkjet method without heating. If composition (X) has a property of decreasing viscosity when heated, composition (X) may be heated and then applied by the inkjet method to be molded. The heating temperature of composition (X) is, for example, 20°C or higher and 50°C or lower.

[0041] When the coating film obtained by molding the composition (X) is irradiated with light to cure, the light irradiated to the coating film is, for example, ultraviolet light. The ultraviolet light means light having a wavelength in the range of 200 nm to 410 nm. The wavelength of the light irradiated to the coating film is preferably in the range of 350 nm to 410 nm, more preferably 385 nm to 405 nm. A representative example of the light irradiated to the coating film is light having a wavelength of 395 nm. The wavelength of the light irradiated to the coating film is not limited to the above description, as long as it can cure the coating film.

[0042] The irradiation intensity of the light irradiated on the coating is 20mW / m 2 More than 20W / cm 2 It is preferable that the irradiation intensity of the light is not limited to the above description, so long as the coating film can be cured.

[0043] The shape of the portion irradiated with light when irradiating the coating film may be an area type having a certain area, or a line type. In the case of a line type, the entire coating film can be irradiated with light by moving the coating film relative to the light source, or by moving the light source relative to the coating film. In this case, it is easy to adjust the time for which the coating film is irradiated with light, and by adjusting this time, it is easy to adjust the integrated light amount.

[0044] More specifically, for example, first, a support substrate 2 is prepared. A partition wall is fabricated on one surface of the support substrate 2 by, for example, a photolithography method using a photosensitive resin material. Next, a plurality of light-emitting elements 4 are provided on one surface of the support substrate 2. The light-emitting elements 4 can be fabricated by an appropriate method such as a vapor deposition method or a coating method. In particular, it is preferable to fabricate the light-emitting elements 4 by a coating method such as an inkjet method. In this way, an element array 9 is fabricated on the support substrate 2.

[0045] Next, a first passivation layer 61 is provided on the element array 9. The first passivation layer 61 can be formed by a deposition method such as a plasma CVD method.

[0046] Next, the composition (X) is formed on the first passivation layer 61 by, for example, an inkjet method to prepare a coating film. If the inkjet method is used for both the formation of the light emitting element 4 and the application of the composition (X), the manufacturing efficiency of the light emitting device 1 can be particularly improved. Next, the coating film is cured by irradiating it with ultraviolet light to prepare the encapsulant 5, which is an optical component. The thickness of the optical component is, for example, 5 μm or more and 50 μm or less.

[0047] The thickness of the optical component is preferably 4 μm or more and 50 μm or less, and more preferably 4 μm or more and 15 μm or less. As described above, in this embodiment, since small droplets of the composition (X) can be easily formed at high density by the inkjet method, it is easy to realize a thin optical component having a thickness of 4 μm or more and 15 μm or less. By thinning the sealing material 5 in this way, tensile stress and compressive stress are less likely to occur in the optical component in the light emitting device 1. Therefore, it is easy to realize a flexible light emitting device 1.

[0048] Before forming a coating film of the composition (X) on the first passivation layer 61, the first passivation layer 61 may be subjected to at least one of atmospheric pressure plasma treatment and UV ozone treatment. In this case, the affinity between the first passivation layer 61 and the composition (X) can be increased. In addition, even if the first passivation layer 61 after the treatment is not subjected to a static elimination treatment, as described above, in this embodiment, since the relative dielectric constant of the photopolymerizable compound (A) at 25°C and a frequency of 10 kHz is 8.0 or less, the trajectory of the droplets of the composition (X) sprayed by the inkjet method is not easily affected by electric fields and magnetic fields. Therefore, defects are unlikely to occur in the coating film and optical components formed from the composition (X). Note that a static elimination treatment may be performed on the first passivation layer 61. If a static elimination treatment is performed, defects are even less likely to occur in the coating film and optical components.

[0049] Next, a second passivation layer 62 is provided on the optical component. The second passivation layer 62 can be formed by a deposition method such as a plasma CVD method.

[0050] Next, an ultraviolet-curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, and then the transparent substrate 3 is placed on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.

[0051] Next, ultraviolet light is irradiated from the outside toward the transparent substrate 3. The ultraviolet light passes through the transparent substrate 3 and reaches the ultraviolet-curable resin material. As a result, the ultraviolet-curable resin material is cured, and the second sealing material 52 is produced.

[0052] The optical component made from the composition (X) according to this embodiment is not limited to the encapsulant 5 for the light emitting element 4. The composition (X) can be used to make various optical components that transmit light emitted by a light source. For example, the optical component may be a color resist. That is, for example, a phosphor may be contained in the composition (X) and a color resist in a color filter may be made from this composition (X). In this case, the color resist in the color filter can be easily made with high density and high accuracy, particularly by using the inkjet method. This color filter can be provided in a display device such as an organic EL display or a micro LED display, which is the light emitting device 1.

[0053] Next, the configuration of a touch panel 100 including the light emitting device 1 and the touch sensor 10 will be described with reference to FIG.

[0054] The light emitting device 1 is, for example, a display device. The touch sensor 10 is disposed on the light emitting device 1. The touch panel 100 further includes a polarizing plate 11 and a protective layer 12. In the touch panel 100, the light emitting device 1, the touch sensor 10, the polarizing plate 11, and the protective layer 12 are laminated in this order.

[0055] The touch sensor 10 is disposed on a transparent substrate 3 included in the light emitting device 1. The touch sensor 10 may be of a capacitance type or a pressure sensitive type. In this embodiment, by making the resin composition (X) have a low dielectric constant, it is easy to suppress malfunction of the touch sensor 10. In particular, when the touch sensor 10 is of a capacitance type, it is easy to suppress malfunction of the touch sensor 10.

[0056] The polarizing plate 11 is disposed on the touch sensor 10. The polarizing plate 11 can improve the visibility of the touch panel 100. The polarizing plate 11 may be in the form of a plate or a film. A known polarizing plate used in a display can be used as the polarizing plate 11. The material of the polarizing plate 11 is not particularly limited, but is, for example, made of a resin.

[0057] The protective layer 12 is disposed on the polarizing plate 11. The polarizing plate 11 can be protected by the protective layer 12. The protective layer 12 may be in the form of a plate or a film. The material of the protective layer 12 is not particularly limited, and is, for example, made of a resin or glass.

[0058] 2. Ultraviolet curable resin composition The components contained in the composition (X) will be described in detail. In the following description, "(meth)acrylic" is a general term for "acrylic" and "methacrylic".

[0059] The photopolymerizable compound (A) is a component that can undergo a polymerization reaction when irradiated with ultraviolet light in the presence or absence of a photopolymerization initiator (B). The photopolymerization initiator (B) may contain a curing catalyst. The photopolymerizable compound (A) contains at least one component selected from the group consisting of, for example, a monomer, an oligomer, and a prepolymer.

[0060] The photopolymerizable compound (A) contains, for example, at least one of a radically polymerizable compound (A1) and a cationic polymerizable compound (W). When the photopolymerizable compound (A) contains a radically polymerizable compound (A1), the photopolymerization initiator (B) preferably contains a photoradical polymerization initiator (B1). When the photopolymerizable compound (A) contains a cationic polymerizable compound (W), the photopolymerization initiator (B) preferably contains a photocationic polymerization initiator (B2) (cationic curing catalyst).

[0061] When the photopolymerizable compound (A) contains a radically polymerizable compound (A1), the radically polymerizable compound (A1) preferably contains an acrylic compound (Y). The acrylic compound (Y) has one or more (meth)acryloyl groups in one molecule.

[0062] The viscosity of the entire acrylic compound (Y) at 25°C is preferably 50 mPa·s or less. In this case, the acrylic compound (Y) can particularly reduce the viscosity of the composition (X). The viscosity of the entire acrylic compound (Y) is more preferably 30 mPa·s or less, and particularly preferably 20 mPa·s or less. The viscosity of the entire acrylic compound (Y) is, for example, 3 mPa·s or more.

[0063] It is also preferable that the viscosity of the entire acrylic compound (Y) at 40°C is 50 mPa·s or less. In this case, the acrylic compound (Y) can particularly reduce the viscosity of the composition (X) when heated. It is more preferable that the viscosity of the entire acrylic compound (Y) is 30 mPa·s or less, and particularly preferable that the viscosity is 20 mPa·s or less. Moreover, the viscosity of the entire acrylic compound (Y) is, for example, 3 mPa·s or more.

[0064] The percentage of the component having a boiling point of 270° C. or more in the acrylic compound (Y) is preferably 80% by mass or more. In this case, the storage stability of the composition (X) is particularly unlikely to be impaired, and outgassing from the cured product is particularly unlikely to occur. It is more preferable that the percentage of the component having a boiling point of 280° C. or more in the acrylic compound (Y) is 80% by mass or more.

[0065] The acrylic compound (Y) preferably contains a component having a viscosity of 20 mPa·s or less at 25° C. In this case, the viscosity of the composition (X) can be particularly reduced.

[0066] The proportion of the component having a viscosity of 20 mPa·s or less at 25°C relative to the total amount of the acrylic compound (Y) is preferably 50% by mass or more and 100% by mass or less. In this case, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can be particularly easily molded by the inkjet method. This proportion is more preferably 60% by mass or more, and even more preferably 70% by mass or more. In addition, this proportion is more preferably 95% by mass or less, and even more preferably 90% by mass or less.

[0067] The component having a viscosity of 20 mPa·s or less at 25°C preferably contains a compound having a glass transition temperature of 80°C or more. In this case, the glass transition temperature of the cured product can be increased while lowering the viscosity of composition (X). It is more preferable that this component contains a compound having a glass transition temperature of 90°C or more, and even more preferable that it contains a compound having a glass transition temperature of 100°C or more. There is no upper limit to the glass transition temperature of the compound contained in this component, but it is, for example, 150°C or less.

[0068] Compounds that the acrylic compound (Y) may contain will be described below.

[0069] The acrylic compound (Y) preferably contains a polyfunctional acrylic compound (Y1) having two or more radically polymerizable functional groups including a (meth)acryloyl group in one molecule. In this case, the polyfunctional acrylic compound (Y1) can increase the glass transition temperature of the cured product, and therefore can increase the heat resistance of the cured product. The proportion of the polyfunctional acrylic compound (Y1) is preferably 50% by mass or more and 100% by mass or less based on the total amount of the acrylic compound (Y). The acrylic compound (Y) may contain only the polyfunctional acrylic compound (Y1).

[0070] Examples of the polyfunctional acrylic compound (Y1) include 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol oligoacrylate, diethylene glycol diacrylate, 1,6-hexanediol oligoacrylate, neopentyl glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, cyclohexane dimethanol diacrylate, tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, bisphenol F polyethoxy diacrylate, pentatriestrol tetraacrylate, propoxylated (2) neopentyl glycol diacrylate, trimethylolpropane triacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, pentaerythritol triacrylate, ethoxylated (3) trimethylol Propane triacrylate, propoxylated (3) glyceryl triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, ethoxylated (4) pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, 2-(2-ethoxyethoxy)ethyl acrylate, hexadiol diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, tripropylene glycol triacrylate, bispentaerythritol hexaacrylate, ethylene glycol diacrylate, 1,6-hexanediol diacrylate, ethoxylated 1,6-hexanediol diacrylate, polypropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,9-nonanediol diacrylate, tetraethylene glycol diacrylate, 2-n-butyl-2-ethyl-1,3-Propanediol diacrylate, hydroxypivalic acid neopentyl glycol diacrylate, hydroxypivalic acid trimethylolpropane triacrylate, ethoxylated phosphoric acid triacrylate, ethoxylated tripropylene glycol diacrylate, neopentyl glycol modified trimethylolpropane diacrylate, stearic acid modified pentaerythritol diacrylate, tetramethylolpropane triacrylate, tetramethylolmethane triacrylate, caprolactone modified trimethylolpropane triacrylate, propoxylated glyceryl triacrylate, tetramethylolmethane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol diacrylate, The composition contains at least one compound selected from the group consisting of erythritol hexaacrylate, caprolactone-modified dipentaerythritol hexaacrylate, dipentaerythritol hydroxypentaacrylate, neopentyl glycol oligoacrylate, trimethylolpropane oligoacrylate, pentaerythritol oligoacrylate, ethoxylated neopentyl glycol di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, and 2-(2-vinyloxyethoxy)ethyl acrylate.

[0071] The acrylic equivalent of the polyfunctional acrylic compound (Y1) is preferably 150 g / eq or less, more preferably 90 g / eq or more and 150 g / eq or less. The weight average molecular weight of the polyfunctional acrylic compound (Y1) is, for example, 100 or more and 1000 or less, more preferably 200 or more and 800 or less.

[0072] The polyfunctional acrylic compound (Y1) preferably contains a compound (Y11) having a structure represented by the following formula (200).

[0073] CH2=CR 1 -COO-(R 3 -O) n-CO-CR 2 =CH2…(200) In formula (200), R 1 and R 2 Each of the groups is a hydrogen atom or a methyl group, n is an integer of 1 or more, R 3 is an alkylene group having 1 or more carbon atoms, and when n is 2 or more, multiple R 3 may be the same or different from each other.

[0074] Compound (Y11) has the structure shown in formula (200), in particular R 3 Since the carbon number of R is 3 or more, it is difficult to increase the affinity of the cured product with water. Therefore, the phosphor (C) is not easily deteriorated by water. 3 The number of carbon atoms in is, for example, 1 or more and 15 or less, preferably 3 or more and 15 or less. In addition, the compound (Y11) can increase the glass transition temperature of the cured product by having the structure shown in formula (200), particularly by having two (meth)acryloyl groups in one molecule, and therefore can increase the heat resistance of the cured product. In addition, n in formula (200) is, for example, an integer of 1 or more and 12 or less.

[0075] The percentage of the compound (Y11) relative to the acrylic compound (Y) is preferably 50% by mass or more. In this case, the affinity of the cured product to water is particularly difficult to increase. The percentage of the compound (Y11) relative to the acrylic compound (Y) is, for example, 100% by mass or less, or 95% by mass or less, preferably 80% by mass or less.

[0076] The compound (Y11) preferably contains a component having a boiling point of 270° C. or higher. That is, the acrylic compound (Y) preferably contains a component having a structure shown in formula (200) and a boiling point of 270° C. or higher. In this case, the acrylic compound (Y) is unlikely to volatilize from the composition (X) during storage of the composition (X) and when the composition (X) is heated. Therefore, the storage stability of the composition (X) is unlikely to be impaired. In addition, even if the compound (Y11) remains unreacted in the cured product of the composition (X), outgassing due to the compound (Y11) is unlikely to occur from the cured product. Therefore, voids due to outgassing are unlikely to occur in the light-emitting device 1. If there are voids in the light-emitting device 1, moisture may penetrate into the light-emitting element 4 through the voids, but if voids are unlikely to occur, moisture is unlikely to penetrate into the light-emitting element 4. The boiling point is a boiling point under normal pressure obtained by converting the boiling point under reduced pressure, and is determined, for example, by the method described in Science of Petroleum, Vol. II, p. 1281 (1938). It is more preferable that the compound (Y11) contains a component having a boiling point of 280° C. or higher.

[0077] The percentage of the compound (Y11) relative to the acrylic compound (Y) is preferably 50% by mass or more. In this case, the storage stability of the composition (X) is effectively improved, the generation of outgassing from the cured product is effectively reduced, and the affinity of the cured product for water is particularly difficult to increase. The percentage of the compound (Y11) relative to the acrylic compound (Y) is, for example, 100% by mass or less, or 95% by mass or less, preferably 80% by mass or less.

[0078] The viscosity of the compound (Y11) at 25°C is preferably 25 mPa·s or less. In this case, the compound (Y11) can reduce the viscosity of the composition (X). The viscosity of the compound (Y11) at 25°C is more preferably 25 mPa·s or less, even more preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. The viscosity of the compound (Y11) at 25°C is, for example, 1 mPa·s or more, preferably 3 mPa·s or more, and even more preferably 5 mPa·s or more.

[0079] The compound (Y11) contains, for example, at least one compound selected from the group consisting of alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, and alkylene oxide-modified alkylene glycol di(meth)acrylate.

[0080] Alkylene glycol di(meth)acrylate is a compound of formula (200) where n is 1. In this case, R 3 The number of carbon atoms in R is preferably 4 to 12. 3may be linear or branched. In particular, the alkylene glycol di(meth)acrylate preferably contains at least one compound selected from the group consisting of 1,4-butanediol diacrylate, 1,3-butylene glycol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butylene glycol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and 1,12-dodecanediol dimethacrylate. In addition, alkylene glycol di(meth)acrylate is Sartomer's product number SR213, Osaka Organic Chemical Industry's product number V195, Sartomer's product number SR212, Sartomer's product number SR247, Kyoei Chemical Industry's product name Light Acrylate NP-A, Sartomer's product number SR238NS, Osaka Organic Chemical Industry's product number V230, Daicel's product number HDDA, Kyoei Chemical Industry's product number 1,6HX-A, Osaka Organic Chemical Industry's product number V260, Kyoei Chemical Industry's product number 1,9-ND-A, Shin-Nakamura Chemical Industry's product number A-NOD-A, Sartomer's product number CD595, Sartomer's product number S It is preferable that the composition contains at least one compound selected from the group consisting of R214NS, product number BD made by Shin-Nakamura Chemical Co., Ltd., product number SR297 made by Sartomer, product number SR248 made by Sartomer, product number Light Ester NP made by Kyoei Chemical Co., Ltd., product number SR239NS made by Sartomer, product name Light Ester 1,6HX made by Kyoei Chemical Co., Ltd., product number HD-N made by Shin-Nakamura Chemical Co., Ltd., product name Light Ester 1,9ND made by Kyoei Chemical Co., Ltd., product number NOD-N made by Shin-Nakamura Chemical Co., Ltd., product name Light Ester 1,10DC made by Kyoei Chemical Co., Ltd., product number DOD-N made by Shin-Nakamura Chemical Co., Ltd., and product number SR262 made by Sartomer.

[0081] Polyalkylene glycol di(meth)acrylate is, for example, a compound represented by formula (200) in which n is 2 or more. n is, for example, 2 to 10, preferably 2 to 7, more preferably 2 to 6, and even more preferably 2 to 3. R 3 The number of carbon atoms is, for example, 2 to 7, and preferably 2 to 5. The larger the number of carbon atoms, the higher the hydrophobicity of the cured product, and the less moisture permeable the cured product becomes. The polyalkylene glycol di(meth)acrylate preferably contains at least one compound selected from the group consisting of diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, hexaethylene glycol dimethacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, tritetramethylene glycol diacrylate, polyethylene glycol 200 dimethacrylate, and polyethylene glycol 200 diacrylate. In addition, the polyalkylene glycol di(meth)acrylate preferably contains at least one compound selected from the group consisting of Sartomer Corporation product number SR230, Sartomer Corporation product number SR508NS, Daicel Corporation product number DPGDA, Sartomer Corporation product number SR306NS, Daicel Corporation product number TPGDA, Osaka Organic Chemical Industry Co., Ltd. product number V310HP, Shin-Nakamura Chemical Co., Ltd. product number APG200, Kyoei Chemical Industry Co., Ltd. product name Light Acrylate PTMGA-250, Sartomer Corporation product number SR231NS, Kyoei Chemical Industry Co., Ltd. product name Light Ester 2EG, Sartomer Corporation product number SR205NS, Kyoei Chemical Industry Co., Ltd. product name Light Ester 3EG, Sartomer Corporation product number SR210NS, Kyoei Chemical Industry Co., Ltd. product name Light Ester 4EG, Mitsubishi Chemical Corporation product name Acrylate HX, and Shin-Nakamura Chemical Co., Ltd. product number 3PG.

[0082] The alkylene oxide modified alkylene glycol di(meth)acrylate includes, for example, propylene oxide modified neopentyl glycol. The alkylene oxide modified alkylene glycol di(meth)acrylate includes, for example, EBECRYL145 manufactured by Daicel Corporation.

[0083] When the acrylic compound (Y) contains a compound (Y11) having a structure represented by formula (200), it is preferable that the compound (Y11) does not contain a compound in which the value of n in formula (200) is 5 or more. (R 3 -O) n is a polyethylene glycol skeleton, it is particularly preferred that the compound (Y11) does not contain a compound having an n value of greater than 5 in formula (200). Even when the compound (Y11) contains a compound having an n value of greater than 5 in formula (200), the percentage of the compound having an n value of greater than 5 in formula (200) relative to the acrylic compound (Y) is preferably 20 mass% or less. Even when the compound (Y11) contains a compound having an n value of greater than 5 in formula (200), it is preferable that the compound (Y11) does not contain a compound having an n value of greater than 9, and more preferably does not contain a compound having an n value of greater than 7. In these cases, the viscosity increase of the composition (X) is particularly unlikely to occur.

[0084] It is particularly preferred that the polyfunctional acrylic compound (Y1) contains a polyalkylene glycol di(meth)acrylate, which has low viscosity and is not easily volatile, and therefore can contribute to lowering the viscosity of the composition (X), improving the storage stability of the composition (X), and reducing outgassing from the cured product.

[0085] When the polyfunctional acrylic compound (Y1) contains polyalkylene glycol di(meth)acrylate, the ratio of polyalkylene glycol di(meth)acrylate to the acrylic compound (Y) is preferably 40% by mass or more and 80% by mass or less. When the ratio of polyalkylene glycol di(meth)acrylate is 40% by mass or more, the viscosity of the composition (X) can be effectively reduced. When the ratio of polyalkylene glycol di(meth)acrylate is 80% by mass or less, the ratio of the compound having three or more (meth)acryloyl groups in the molecule increases, and the reactivity of the composition (X) and the glass transition temperature of the cured product can be increased. This ratio is more preferably 42% by mass or more and 75% by mass or less, and even more preferably 45% by mass or more and 70% by mass or less.

[0086] The polyfunctional acrylic compound (Y1) may contain a compound having three or more radical polymerizable functional groups, including a (meth)acryloyl group, in one molecule. In this case, the polyfunctional acrylic compound (Y1) may contain at least one selected from the group consisting of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and pentaerythritol tetra(meth)acrylate. In this case, the glass transition temperature of the cured product can be particularly increased, and therefore the heat resistance of the cured product can be particularly increased.

[0087] The polyfunctional acrylic compound (Y1) preferably contains pentaerythritol tetra(meth)acrylate. In this case, the glass transition temperature of the cured product can be particularly increased, and the reactivity of the composition (X) can be improved. When the reactivity of the composition (X) is improved, the composition (X) can be easily cured in an oxygen-containing environment such as the air atmosphere.

[0088] When the polyfunctional acrylic compound (Y1) contains pentaerythritol tetra(meth)acrylate, the ratio of pentaerythritol tetra(meth)acrylate to the acrylic compound (Y) is preferably 0.5% by mass or more and 10% by mass or less. In this case, the composition (X) can achieve both high reactivity and low viscosity. This ratio is more preferably 1% by mass or more and 9% by mass or less, and even more preferably 2% by mass or more and 8% by mass or less.

[0089] The polyfunctional acrylic compound (Y1) may have at least one of a benzene ring, an alicyclic ring, and a polar group. The polar group is, for example, at least one of an OH group and an NHCO group. In this case, the shrinkage during curing of the composition (X) can be particularly reduced. Furthermore, the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide can also be increased. The polyfunctional acrylic compound (Y1) preferably contains at least one compound selected from the group consisting of tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, bisphenol F polyethoxy diacrylate, trimethylolpropane triacrylate, and pentaerythritol triacrylate. These compounds can particularly reduce the shrinkage during curing of the composition (X). Furthermore, these compounds can also increase the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide.

[0090] When the adhesion between the cured product and the inorganic material is increased, in the case where the color resist 1 is overlaid on a film made of an inorganic material (inorganic film) such as a SiN film, high adhesion between the color resist 1 and the inorganic film is easily obtained. In addition, strictly speaking, since the adhesion between the resin matrix in which the photopolymerizable compound (A) is cured and the inorganic compound is increased, in the case where the phosphor (C) is an inorganic particle such as the quantum dot phosphor (C1), the adhesion between the resin matrix and the phosphor (C) in the cured product is likely to be increased.

[0091] It is particularly preferred that the polyfunctional acrylic compound (Y1) contains polyalkylene glycol di(meth)acrylate and pentaerythritol tetra(meth)acrylate. In this case, the composition (X) has low viscosity and excellent reactivity. Therefore, the composition (X) can be easily cured in an oxygen-containing environment such as the air atmosphere.

[0092] The acrylic compound (Y) preferably contains a monofunctional acrylic compound (Y2) having only one (meth)acryloyl group as a radical polymerizable functional group in one molecule. The monofunctional acrylic compound (Y2) can suppress shrinkage of the composition (X) during curing.

[0093] The amount of the monofunctional acrylic compound (Y2) relative to the total amount of the acrylic compound (Y) is preferably more than 0% by mass and not more than 50% by mass. If the amount of the monofunctional acrylic compound (Y2) is more than 0% by mass, the shrinkage during curing of the composition (X) can be suppressed. In addition, if the amount of the monofunctional acrylic compound (Y2) is 50% by mass or less, the amount of the polyfunctional acrylic compound (Y1) can be 50% by mass or more, and the heat resistance of the cured product can be particularly improved. It is more preferable that the amount of the monofunctional acrylic compound (Y2) is 5% by mass or more, and it is also more preferable that it is 30% by mass or less.

[0094] Examples of the monofunctional acrylic compound (Y2) include tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, isobutyl acrylate, t-butyl acrylate, isooctyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, 3-methoxybutyl acrylate, ethoxyethyl acrylate, butoxyethyl acrylate, ethoxydiethylene glycol acrylate, and methacrylate. Toxidixylethyl acrylate, ethyl diglycol acrylate, cyclic trimethylolpropane formal monoacrylate, imide acrylate, isoamyl acrylate, ethoxylated succinic acid acrylate, trifluoroethyl acrylate, ω-carboxypolycaprolactone monoacrylate, cyclohexyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, stearyl acrylate, diethylene glycol monobutyl ether acrylate, lauryl acrylate, isodecyl acrylate, 3,3,5-trimethylcyclohexanol acrylate, isooctyl acrylate, octyl / decyl acrylate, tridecyl acrylate, caprolactone acrylate, ethoxylated (4)nylphenol acrylate, methoxypolyethylene glycol (350) monoacrylate, methoxypolyethylene glycol (550) monoacrylate, phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-t-butylcyclohexyl acrylate, caprolactone modified tetrahydrofurfuryl acrylate, tributary The composition contains at least one compound selected from the group consisting of bromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, an ethylene oxide adduct of 2-phenoxyethyl acrylate, a propylene oxide adduct of 2-phenoxyethyl acrylate, acryloylmorpholine, morpholin-4-yl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 1,4-cyclohexanedimethanol monoacrylate, 3-methacryloyloxymethylcyclohexene oxide, and 3-acryloyloxymethylcyclohexene oxide.

[0095] The monofunctional acrylic compound (Y2) may contain at least one compound selected from the group consisting of compounds having an alicyclic structure and compounds having a cyclic ether structure.

[0096] The compound having an alicyclic structure contains at least one compound selected from the group consisting of, for example, phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-t-butylcyclohexyl acrylate, caprolactone-modified tetrahydrofurfuryl acrylate, tribromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, an ethylene oxide adduct of 2-phenoxyethyl acrylate, a propylene oxide adduct of 2-phenoxyethyl acrylate, acryloylmorpholine, morpholin-4-yl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, and 1,4-cyclohexanedimethanol monoacrylate.

[0097] The number of ring members in the cyclic ether structure in the compound having a cyclic ether structure is preferably 3 or more, more preferably 3 to 4. The number of carbon atoms contained in the cyclic ether structure is preferably 2 to 9, more preferably 2 to 6. The compound having a cyclic ether structure contains, for example, at least one compound selected from the group consisting of 3-methacryloyloxymethylcyclohexene oxide and 3-acryloyloxymethylcyclohexene oxide.

[0098] The acrylic compound (Y) may contain a compound having silicon in the molecular skeleton. In this case, the adhesion between the cured product and the inorganic material is improved. The compound having silicon in the molecular skeleton contains at least one compound selected from the group consisting of 3-(trimethoxysilyl)propyl acrylate (e.g., product number KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.) and (meth)acrylic group-containing alkoxysilane oligomer (e.g., product number KR-513 manufactured by Shin-Etsu Chemical Co., Ltd.).

[0099] The acrylic compound (Y) may contain a compound having phosphorus in the molecular skeleton. In this case, the adhesion between the cured product and the inorganic material is improved. The compound having phosphorus in the molecular skeleton includes, for example, acid phosphoxy (meth)acrylate, such as acid phosphoxy polyoxypropylene glycol monomethacrylate.

[0100] The acrylic compound (Y) may contain a compound having nitrogen in the molecular skeleton. In this case, the adhesion between the cured product and the inorganic material is improved. In addition, the reactivity of the acrylic compound (Y) is easily improved, so that outgassing from the cured product is less likely to occur. The compound having nitrogen in the molecular skeleton includes at least one compound selected from the group consisting of compounds having a morpholine skeleton, such as acryloylmorpholine and morpholin-4-yl acrylate, diethylacrylamide, dimethylaminopropylacrylamide, and pentamethylpiperidyl methacrylate.

[0101] It is particularly preferred that the acrylic compound (Y) contains a compound having a morpholine skeleton. In this case, the reactivity of the composition (X) can be further improved, and the curability of the composition (X) under an air atmosphere can be further enhanced. It is particularly preferred that the acrylic compound (Y) contains at least one of acryloylmorpholine and morpholin-4-yl acrylate. In this case, the shrinkage during curing of the composition (X) can be suppressed. In addition, the viscosity of acryloylmorpholine and morpholin-4-yl acrylate is low, and therefore these compounds are unlikely to increase the viscosity of the composition (X). Furthermore, since these compounds are unlikely to volatilize, it is easy to improve the storage stability of the composition (X).

[0102] The ratio of the compound having a morpholine skeleton to the acrylic compound (Y) is preferably 5% by mass or more and 50% by mass or less. In this case, there is an advantage that outgassing is less likely to occur from the cured product of the composition (X). This ratio is more preferably 7% by mass or more and 45% by mass or less, and even more preferably 10% by mass or more and 40% by mass or less.

[0103] The acrylic compound (Y) may contain a compound having an isobornyl skeleton. The compound having an isobornyl skeleton may contain, for example, one or more compounds selected from the group consisting of isobornyl acrylate and isobornyl methacrylate.

[0104] The acrylic compound (Y) may contain a component consisting of a compound having at least one skeleton selected from the group consisting of a dicyclopentadiene skeleton, a dicyclopentanyl skeleton, a dicyclopentenyl skeleton, and a bisphenol skeleton. Specifically, the acrylic compound (Y) may contain at least one compound selected from the group consisting of, for example, tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, and bisphenol F polyethoxy diacrylate. In this case, the adhesion between the cured product and the inorganic material can be increased.

[0105] The acrylic compound (Y) may contain a compound represented by the following formula (100). In this case, the reactivity of the composition (X) can be increased, and the adhesion between the cured product and the inorganic material can be improved.

[0106] [ka]

[0107] In formula (100), R 0 is H or a methyl group. X is a single bond or a divalent hydrocarbon group. R 1 From R 11 Each of is H, an alkyl group or -R 12 -OH, R 12 is an alkylene group and R 1 From R 11 At least one of the groups is an alkyl group or -R 12 -OH. 1 From R 11 are not chemically bonded to each other.

[0108] Specifically, for example, the acrylic compound (Y) may contain at least one compound selected from the group consisting of a compound represented by the following formula (110), a compound represented by the following formula (120), and a compound represented by the following formula (130).

[0109] [ka]

[0110] The radical polymerizable compound (A1) may contain a radical polymerizable compound (Z) other than the acrylic compound (Y). The amount of the radical polymerizable compound (Z) relative to the total amount of the acrylic compound (Y) and the radical polymerizable compound (Z) is, for example, 10 mass% or less. The radical polymerizable compound (Z) may contain either one or both of a polyfunctional radical polymerizable compound (Z1) having two or more radical polymerizable functional groups in one molecule and a monofunctional radical polymerizable compound (Z2) having only one radical polymerizable functional group in one molecule. The polyfunctional radical polymerizable compound (Z1) may contain at least one compound selected from the group consisting of an aromatic urethane oligomer, an aliphatic urethane oligomer, an epoxy acrylate oligomer, a polyester acrylate oligomer, and other special oligomers having two or more ethylenic double bonds in one molecule. Note that the components that the polyfunctional radical polymerizable compound (Z1) may contain are not limited to those mentioned above. The monofunctional radical polymerizable compound (Z2) contains at least one compound selected from the group consisting of, for example, N-vinylformamide, vinylcaprolactam, vinylpyrrolidone, phenylglycidyl ether, p-tert-butylphenylglycidyl ether, butylglycidyl ether, 2-ethylhexylglycidyl ether, allylglycidyl ether, 1,2-butylene oxide, 1,3-butadiene monoxide, 1,2-epoxydodecane, epichlorohydrin, 1,2-epoxydecane, styrene oxide, cyclohexene oxide, 3-vinylcyclohexene oxide, 4-vinylcyclohexene oxide, N-vinylpyrrolidone and N-vinylcaprolactam. Note that the components that the monofunctional radical polymerizable compound (Z2) can contain are not limited to the above.

[0111] When the radical polymerizable compound (A1) contains a radical polymerizable compound (Z), the radical polymerizable compound (Z) may contain a compound having nitrogen in its molecular skeleton. The compound having nitrogen in its molecular skeleton includes at least one compound selected from the group consisting of N-vinylformamide, N-vinylpyrrolidone, and N-vinylcaprolactam. In this case, the adhesion between the cured product and the inorganic material is improved, similarly to the case where the acrylic compound (Y) contains a compound having nitrogen in its molecular skeleton.

[0112] In other words, the radical polymerizable compound (A1) preferably contains a compound having nitrogen in the molecular skeleton. The compound having nitrogen in the molecular skeleton may contain a compound contained in the acrylic compound (Y) or may contain a compound contained in the radical polymerizable compound (Z). In this case, the adhesion between the cured product and the inorganic material is improved. The ratio of the compound having nitrogen in the molecular skeleton to the entire radical polymerizable compound (A1) is preferably 5% by mass or more and 80% by mass or less. When this ratio is 5% by mass or more, the adhesion between the cured product and the inorganic material is particularly likely to be improved. When this ratio is 80% by mass or less, the compound having nitrogen in the molecular skeleton is less likely to inhibit the storage stability of the composition (X) and is less likely to generate satellites when the composition (X) is sprayed by the inkjet method. Therefore, the inkjet properties of the composition (X) are less likely to be inhibited. Furthermore, outgassing caused by the compound having nitrogen in the molecular skeleton can be less likely to occur. This ratio is more preferably 10% by mass or more and 70% by mass or less, even more preferably 20% by mass or more and 60% by mass or less, and particularly preferably 25% by mass or more and 50% by mass.

[0113] When the photopolymerizable compound (A) contains a cationic polymerizable compound (W), the cationic polymerizable compound (W) contains, for example, at least one of a polyfunctional cationic polymerizable compound (W1) and a monofunctional cationic polymerizable compound (W2).

[0114] The polyfunctional cationically polymerizable compound (W1) can contain either one or both of a polyfunctional cationically polymerizable compound (W11) having no siloxane skeleton and a polyfunctional cationically polymerizable compound (W12) having a siloxane skeleton.

[0115] The polyfunctional cationically polymerizable compound (W11) does not have a siloxane skeleton and has two or more cationically polymerizable functional groups per molecule. The number of cationically polymerizable functional groups per molecule of the polyfunctional cationically polymerizable compound (W11) is preferably 2 to 4, and more preferably 2 to 3.

[0116] The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.

[0117] The polyfunctional cationically polymerizable compound (W11) contains at least one compound selected from the group consisting of, for example, polyfunctional alicyclic epoxy compounds, polyfunctional heterocyclic epoxy compounds, polyfunctional oxetane compounds, alkylene glycol diglycidyl ethers, and alkylene glycol monovinyl monoglycidyl ethers.

[0118] The polyfunctional alicyclic epoxy compound contains, for example, either one or both of a compound represented by the following formula (1) and a compound represented by the following formula (20).

[0119] [ka]

[0120] In formula (1), R 1 ~R 18 Each of the groups is independently a hydrogen atom, a halogen atom, or a hydrocarbon group. R is a group. The number of carbon atoms in the hydrocarbon group is preferably within the range of 1 to 20. Examples of the hydrocarbon group include alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, and propyl groups; alkenyl groups having 2 to 20 carbon atoms, such as vinyl and allyl groups; and alkylidene groups having 2 to 20 carbon atoms, such as ethylidene and propylidene groups. The hydrocarbon group may contain an oxygen atom or a halogen atom. 1 ~R 18 Each of the is independently preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.

[0121] In formula (1), X is a single bond or a divalent organic group, and the organic group is, for example, -CO-O-CH2-.

[0122] Examples of the compound represented by formula (1) include a compound represented by the following formula (1a) and a compound represented by the following formula (1b).

[0123] [ka]

[0124] [ka]

[0125] [ka]

[0126] In formula (20), R 1 ~R 12are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 20 carbon atoms. The halogen atom is, for example, a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom. The hydrocarbon group having 1 to 20 carbon atoms is, for example, an alkyl group having 1 to 20 carbon atoms such as a methyl group, an ethyl group, or a propyl group; an alkenyl group having 2 to 20 carbon atoms such as a vinyl group or an allyl group; or an alkylidene group having 2 to 20 carbon atoms such as an ethylidene group or a propylidene group. The hydrocarbon group having 1 to 20 carbon atoms may contain an oxygen atom or a halogen atom.

[0127] R 1 ~R 12 Each of these is preferably independently a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms. It is preferably a hydrogen atom or a methyl group, more preferably a hydrogen atom, and most preferably a hydrogen atom.

[0128] An example of the compound represented by formula (20) includes the tetrahydroindene diepoxide represented by formula (20a) below.

[0129] [ka]

[0130] The polyfunctional heterocyclic epoxy compound contains, for example, a trifunctional epoxy compound as shown in the following formula (2).

[0131] [ka]

[0132] The polyfunctional oxetane compound contains, for example, a bifunctional oxetane compound as shown in the following formula (3).

[0133] [ka]

[0134] The alkylene glycol diglycidyl ether contains at least one compound selected from the group consisting of compounds represented by the following formulas (4) to (7).

[0135] [ka]

[0136] [ka]

[0137] [ka]

[0138] [ka]

[0139] The alkylene glycol monovinyl monoglycidyl ether contains, for example, a compound represented by the following formula (8).

[0140] [ka]

[0141] More specifically, the polyfunctional cationically polymerizable compound (W11) may contain at least one component selected from the group consisting of, for example, CELLOXIDE 2021P and CELLOXIDE 8010 manufactured by Daicel, TEPIC-VL manufactured by Nissan Chemical, OXT-221 manufactured by Toagosei, and 1,3-PD-DEP, 1,4-BG-DEP, 1,6-HD-DEP, NPG-DEP, and butylene glycol monovinyl monoglycidyl ether manufactured by Yokkaichi Chemical.

[0142] It is also preferred that the polyfunctional cationically polymerizable compound (W11) contains a polyfunctional alicyclic epoxy compound, in which case the composition (X) can have particularly high cationic polymerization reactivity.

[0143] The polyfunctional alicyclic epoxy compound preferably contains either one or both of the compound represented by formula (1) and the compound represented by formula (20). In this case, the composition (X) can have higher cationic polymerization reactivity.

[0144] When the polyfunctional alicyclic epoxy compound contains a compound represented by formula (1), the compound represented by formula (1) preferably contains a compound represented by formula (1a). In this case, the composition (X) can have a higher cationic polymerization reactivity and a particularly low viscosity.

[0145] In addition, since the compound represented by formula (20) has a low viscosity, the composition (X) can have good UV curing properties and a particularly low viscosity when the composition (X) contains the compound represented by formula (20). Furthermore, the compound represented by formula (20) has a low viscosity but is not easily volatilized. Therefore, even if the composition (X) contains the compound represented by formula (20), the composition (X) is not easily changed in composition due to the volatilization of the compound represented by formula (20). Therefore, the composition (X) can have a low viscosity without impairing storage stability by containing the compound represented by formula (20).

[0146] The compound represented by formula (20) can be synthesized, for example, by oxidizing a cyclic olefin compound having a tetrahydroindene skeleton with an oxidizing agent.

[0147] The compound represented by formula (20) may contain four stereoisomers based on the stereoconfiguration of the two epoxy rings. The compound represented by formula (20) may contain any of the four stereoisomers. That is, the compound represented by formula (20) may contain at least one component selected from the group consisting of the four stereoisomers. In the compound represented by formula (20), the total amount of the exo-endo isomer and the endo-endo isomer among the four stereoisomers is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total epoxy compound (A1). In this case, the heat resistance of the cured product can be improved. The ratio of a specific stereoisomer in the compound represented by formula (20) can be determined based on the peak area ratio appearing in a chromatogram obtained by gas chromatography.

[0148] In order to reduce the amount of exo-endo isomer and endo-endo isomer in the compound represented by formula (20), an appropriate method can be applied, such as a method of subjecting the compound represented by formula (20) to precision distillation or a method of applying column chromatography using silica gel or the like as a packing material.

[0149] When the composition (X) contains a polyfunctional cationic polymerizable compound (W11), the ratio of the polyfunctional cationic polymerizable compound (W11) to the total amount of the resin components is preferably within the range of 5 to 95% by mass. The resin components refer to compounds having cationic polymerizability in the composition (X), and include the polyfunctional cationic polymerizable compound (W1) and the monofunctional cationic polymerizable compound (W2). When the ratio of the polyfunctional cationic polymerizable compound (W11) is 5% by mass or more, the composition (X) can have particularly excellent reactivity during the photocationic polymerization reaction, and the cured product can have high strength (hardness). When the ratio of the polyfunctional cationic polymerizable compound (W11) is 95% by mass or less, when the composition (X) contains a moisture absorbent (E), the moisture absorbent (E) can be particularly easily dispersed uniformly in the composition (X). The proportion of this polyfunctional cationic polymerizable compound (W11) is more preferably 12% by mass or more, even more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more. The proportion of this polyfunctional cationic polymerizable compound (W11) is more preferably 85% by mass or less, even more preferably 60% by mass or less. For example, the proportion of the polyfunctional cationic polymerizable compound (W11) is preferably within the range of 20 to 60% by mass.

[0150] When the polyfunctional cationic polymerizable compound (W11) contains a polyfunctional alicyclic epoxy compound, the polyfunctional alicyclic epoxy compound may be a part or the whole of the polyfunctional cationic polymerizable compound (W11). The ratio of the polyfunctional alicyclic epoxy compound to the polyfunctional cationic polymerizable compound (W11) is preferably within the range of 15 to 100 mass%. When this ratio is 15 mass% or more, the polyfunctional alicyclic epoxy compound can particularly contribute to improving the ultraviolet curing property of the composition (X).

[0151] The polyfunctional cationic polymerizable compound (W12) has a siloxane skeleton and two or more cationic polymerizable functional groups per molecule. The number of cationic polymerizable functional groups per molecule of the polyfunctional cationic polymerizable compound (W12) is preferably 2 to 6, more preferably 2 to 4. The polyfunctional cationic polymerizable compound (W12) can contribute to improving the cationic polymerization reactivity of the composition (X) and can also contribute to improving the heat discoloration resistance of the cured product and optical components. The polyfunctional cationic polymerizable compound (W12) can also contribute to lowering the elastic modulus of the cured product and optical components. When the composition (X) contains a moisture absorbent (E), the polyfunctional cationic polymerizable compound (W12) can also contribute to improving the dispersibility of the moisture absorbent (E) in the composition (X) and the cured product.

[0152] The polyfunctional cationically polymerizable compound (W12) is preferably a liquid at 25° C. In particular, the viscosity of the polyfunctional cationically polymerizable compound (W12) at 25° C. is preferably within the range of 10 to 300 mPa s. In this case, an increase in the viscosity of the composition (X) can be suppressed.

[0153] The cationically polymerizable functional group contained in the polyfunctional cationically polymerizable compound (W12) is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.

[0154] The siloxane skeleton of the polyfunctional cationic polymerizable compound (W12) may be linear, branched, or cyclic. The number of Si atoms in the siloxane skeleton is preferably within the range of 2 to 14. In this case, the composition (X) can have a particularly low viscosity. The number of Si atoms is more preferably within the range of 2 to 10, even more preferably within the range of 2 to 7, and particularly preferably within the range of 3 to 6.

[0155] The polyfunctional cationically polymerizable compound (W12) contains, for example, at least one of a compound represented by formula (10) and a compound represented by formula (11).

[0156] [ka]

[0157] [ka]

[0158] In each of formulas (10) and (11), R is a single bond or a divalent organic group, and is preferably an alkylene group. Y is a siloxane skeleton, which may be linear, branched, or cyclic, and the number of Si atoms is preferably within a range of 2 to 14, more preferably within a range of 2 to 10, even more preferably within a range of 2 to 7, and particularly preferably within a range of 3 to 6. n is an integer of 2 or more, and is preferably within a range of 2 to 4.

[0159] More specifically, for example, the polyfunctional cationically polymerizable compound (W12) contains a compound represented by the following formula (10a).

[0160] [ka]

[0161] R in formula (10a) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (10a) is an integer of 0 or more. n is preferably within the range of 0 to 12, more preferably within the range of 0 to 8, even more preferably within the range of 0 to 5, and particularly preferably within the range of 1 to 4.

[0162] The compound represented by formula (10a) preferably contains a compound represented by the following formula (30): That is, the polyfunctional cationically polymerizable compound (W12) preferably contains a compound represented by the following formula (30).

[0163] [ka]

[0164] More specifically, the polyfunctional cationically polymerizable compound (W12) preferably contains at least one component selected from the group consisting of product numbers X-40-2669, X-40-2670, X-40-2715, X-40-2732, X-22-169AS, X-22-169B, X-22-2046, X-22-343, X-22-163, and X-22-163B manufactured by Shin-Etsu Chemical Co., Ltd.

[0165] The polyfunctional cationic polymerizable compound (W12) preferably has an alicyclic epoxy structure, and it is particularly preferred that the polyfunctional cationic polymerizable compound (W12) contains a compound represented by formula (10a). The compound represented by formula (10a) can particularly contribute to improving the cationic polymerization reactivity and lowering the viscosity of the composition (X), and can also particularly contribute to improving the heat discoloration resistance and lowering the elastic modulus of the cured product and optical components. When the composition (X) contains a moisture absorbent (E), it can also particularly contribute to improving the dispersibility of the moisture absorbent (E) in the composition (X).

[0166] When the composition (X) contains a polyfunctional cationically polymerizable compound (W12), the ratio of the polyfunctional cationically polymerizable compound (W12) to the total amount of the resin components is preferably within the range of 5 to 95 mass %. In this case, when the composition (X) contains a moisture absorbent (E), the dispersibility of the moisture absorbent (E) in the composition (X) and in the cured product is particularly improved, and the composition (X) can have a particularly high photocationic polymerization reactivity.

[0167] The monofunctional cationically polymerizable compound (W2) has only one cationically polymerizable functional group per molecule. The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.

[0168] The viscosity of the monofunctional cationic polymerizable compound (W2) at 25°C is preferably 8 mPa·s or less. In this case, even if the composition (X) does not contain a solvent, the monofunctional cationic polymerizable compound (W2) can reduce the viscosity of the composition (X). In particular, the viscosity of the monofunctional cationic polymerizable compound (W2) at 25°C is preferably within the range of 0.1 to 8 mPa·s.

[0169] The monofunctional cationically polymerizable compound (W2) may contain, for example, at least one compound selected from the group consisting of the compounds represented by the following formulas (12) to (17) and limonene oxide.

[0170] [ka]

[0171] [ka]

[0172] [ka]

[0173] [ka]

[0174] [ka]

[0175] [ka]

[0176] The ratio of the monofunctional cationic polymerizable compound (W2) to the total amount of the resin components is preferably within the range of 5 to 50% by mass. If the ratio of the monofunctional cationic polymerizable compound (W2) is 5% by mass or more, the viscosity of the composition (X) can be particularly reduced. If the ratio of the monofunctional cationic polymerizable compound (W2) is 50% by mass or less, the composition (X) can have particularly excellent reactivity during the photocationic polymerization reaction, and the cured product can have high strength (hardness). The ratio of this monofunctional cationic polymerizable compound (W2) is more preferably 10% by mass or more, and even more preferably 15% by mass or more. The ratio of this monofunctional cationic polymerizable compound (W2) is more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less. If the proportion of the monofunctional cationic polymerizable compound (W2) is particularly 35% by mass or less, the amount of volatilization of the components in the composition (X) during storage of the composition (X) can be effectively reduced, and therefore the properties of the composition (X) are less likely to be impaired even if the composition (X) is stored for a long period of time. Furthermore, the occurrence of tack in the cured product can be particularly suppressed. For example, the proportion of the monofunctional cationic polymerizable compound (W2) is preferably within the range of 10 to 35% by mass.

[0177] In particular, when the composition (X) contains a polyfunctional cationic polymerizable compound (W11) and a polyfunctional cationic polymerizable compound (W12), the ratio of the polyfunctional cationic polymerizable compound (W11) is preferably within the range of 30-60 mass%, the ratio of the polyfunctional cationic polymerizable compound (W12) is preferably within the range of 15-30 mass%, and the ratio of the monofunctional cationic polymerizable compound (W2) is preferably within the range of 15-40 mass% based on the total amount of the resin components. In this case, the composition (X) can achieve a good balance of good storage stability, low viscosity, and good cationic polymerization reactivity, and further achieve a good balance of excellent transparency, excellent hygroscopicity, and high refractive index of the cured product.

[0178] When the cationically polymerizable compound (W) contains the compound represented by formula (3) and the compound represented by formula (16), by adjusting the ratio of the two, it is possible to appropriately adjust the ease of progress of the curing reaction when preparing a photocured product from the composition (X), while achieving a low viscosity and improved storage stability of the composition (X).

[0179] The amount of the compound represented by formula (16) is appropriately adjusted so that the composition (X) has the above-mentioned properties. For example, the amount of the compound represented by formula (16) is preferably 10 mass % or more and 40 mass % or less based on the total amount of the resin components.

[0180] The cationically polymerizable compound (W) preferably contains a compound (f1) represented by the following formula (30) (hereinafter also referred to as aromatic epoxy compound (f1)).

[0181] [ka]

[0182] In formula (30), X is at least one selected from the group consisting of halogen, H, a hydrocarbon group, and an alkylene glycol group, and when there are multiple Xs in one molecule, they may be the same or different from each other. The hydrocarbon group is, for example, an alkyl group or an aryl group. When X is a hydrocarbon group, the carbon number of X is, for example, in the range of 1 to 10. R is a single bond or a divalent organic group. When R is a divalent organic group, the divalent organic group is, for example, an alkylene group, an oxyalkylene group, a carbonyloxyalkylene group (for example, -CO-O-CH2-), or a -C(Ph)2-O-CH2- group. Y is H or a monovalent organic group. When Y is a monovalent organic group, the monovalent organic group is, for example, an alkyl group or an aryl group.

[0183] When the cationic polymerizable compound (W) contains an aromatic epoxy compound (f1), the aromatic epoxy compound (f1) has a low viscosity, so that the aromatic epoxy compound (f1) tends to lower the viscosity of the composition (X). In addition, the aromatic epoxy compound (f1) is not easily volatilized, so that even if the composition (X) is stored, the composition (X) is not easily changed in composition due to the volatilization of the aromatic epoxy compound (f1). Therefore, the aromatic epoxy compound (f1) tends to increase the storage stability of the composition (X). In addition, the aromatic epoxy compound (f1) has high reactivity, so that unreacted components are not easily left in the cured product, so that outgassing is not easily generated from the cured product. Furthermore, the aromatic epoxy compound (f1) tends to increase the glass transition temperature of the cured product, so that the heat resistance of the cured product is easily increased.

[0184] In addition, the aromatic epoxy compound (f1) is less likely to produce defective droplets called satellites when the composition (X) is discharged by an inkjet method. A satellite is a droplet that separates from the original droplet and adheres to a position on the coating target different from the original droplet's adhesion position when the droplet is discharged by an inkjet method. The occurrence of satellites leads to a deterioration in the dimensional accuracy of the cured product produced from the composition (X).

[0185] R in formula (30) is preferably a single bond or an alkylene group. When n in formula (30) is 2 or 3, at least one of the multiple R in formula (30) is preferably a single bond or an alkylene group. In these cases, the reactivity of the aromatic epoxy compound (f1) tends to be high, and therefore the curability of the composition (X) tends to be high when the composition (X) is irradiated with ultraviolet light.

[0186] The aromatic epoxy compound (f1) preferably contains at least one compound selected from the group consisting of the compounds represented by the following formulas (301) to (318).

[0187] [ka]

[0188] In particular, it is preferred that the aromatic epoxy compound (f1) contains at least one component selected from the group consisting of the compounds represented by the formulas (301) to (305), (312), (314), and (318). These compounds tend to have high reactivity because at least one epoxy group (oxirane) in the compound is bonded to a benzene ring via a single bond or an alkylene group, and therefore tend to enhance the curability of the composition (X).

[0189] The ratio of the aromatic epoxy compound (f1) to the entire cationic polymerizable compound (W) is preferably 5% by mass or more. In this case, the above-mentioned effect of the aromatic epoxy compound (f1) is particularly easily obtained. This ratio is also preferably 95% by mass or less. In this case, the storage property of the composition (X) is likely to be good. This ratio is more preferably 10% by mass or more and 90% by mass or less, and even more preferably 20% by mass or more and 85% by mass or less.

[0190] Preferred compounds that the photopolymerizable compound (A) may contain are as described above, and in this embodiment, as described above, the photopolymerizable compound (A) has a relative dielectric constant of 8.0 or less at 25° C. and a frequency of 10 kHz, and a viscosity of 50 mPa s or less at 25° C. Therefore, it is preferable that the photopolymerizable compound (A) contains a compound having a low relative dielectric constant and a low viscosity. In particular, it is preferable that the photopolymerizable compound (A) contains at least one compound selected from the group consisting of isobornyl acrylate, isobornyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, adamantyl acrylate, adamantyl methacrylate, methyl acrylate, butyl acrylate, lauryl acrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, 3-allyloxymethyl-3-ethyloxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 2-ethylhexyloxetane, 1,4-cyclohexanedimethanol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether.

[0191] The photopolymerizable compound (A) preferably contains a component (P) consisting of at least one compound having a dielectric constant of 7.0 or less at 25°C and a frequency of 10 kHz and a viscosity of 50 mPa·s or less at 25°C. The component (P) particularly easily reduces the dielectric constant and viscosity of the photopolymerizable compound (A). The component (P) preferably contains at least one compound selected from the group consisting of isobornyl acrylate, isobornyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, adamantyl acrylate, adamantyl methacrylate, methyl acrylate, butyl acrylate, lauryl acrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, and 1,4-cyclohexanedimethanol divinyl ether.

[0192] The ratio of component (P) to photopolymerizable compound (A) is preferably 50% by mass or more. In this case, component (P) is particularly easy to reduce the relative dielectric constant of photopolymerizable compound (A) and particularly easy to reduce the viscosity. In order to reduce the relative dielectric constant and viscosity of photopolymerizable compound (A), the ratio of component (P) is ideally 100% by mass. Of course, for the purpose of adjusting properties other than the relative dielectric constant and viscosity of photopolymerizable compound (A), photopolymerizable compound (A) may contain a compound other than component (P). In that case, the ratio of component (P) to photopolymerizable compound (A) is, for example, 80% by mass or less.

[0193] The ratio of the compound having a dielectric constant of more than 7.0 at 25°C and a frequency of 10kHz in the photopolymerizable compound (A) is preferably 0% by mass or more and 13% by mass or less with respect to the photopolymerizable compound (A). In this case, it is particularly easy to lower the dielectric constant of the photopolymerizable compound. In order to reduce the dielectric constant of the photopolymerizable compound (A), the ratio of the compound having a dielectric constant of more than 7.0 at 25°C and a frequency of 10kHz is ideally 0% by mass. Of course, for the purpose of adjusting properties other than the dielectric constant of the photopolymerizable compound (A), the photopolymerizable compound (A) may contain a compound having a dielectric constant of more than 7.0 at 25°C and a frequency of 10kHz. In that case, the ratio of the compound having a dielectric constant of more than 7.0 at 25°C and a frequency of 10kHz with respect to the photopolymerizable compound (A) is, for example, 5% by mass or more.

[0194] As described above, when the photopolymerizable compound (A) contains the radical polymerizable compound (A1), the photopolymerization initiator (B) preferably contains the photoradical polymerization initiator (B1). The photoradical polymerization initiator (B1) is not particularly limited as long as it is a compound that generates radical species when irradiated with ultraviolet light. The photoradical polymerization initiator (B1) contains at least one compound selected from the group consisting of, for example, aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, thio compounds (thioxanthone compounds, thiophenyl group-containing compounds, etc.), hexaarylbiimidazole compounds, oxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds. The amount of the photoradical polymerization initiator (B1) relative to 100 parts by mass of the composition (X) is, for example, 1 part by weight or more and 10 parts by mass or less.

[0195] The photoradical polymerization initiator (B1) preferably contains an initiator having photobleaching properties, which tends to increase the light transmittance of the cured product.

[0196] The photobleachable initiator contains, for example, at least one of an oxime ester compound and an acylphosphine oxide compound, both of which have photobleachable properties.

[0197] The oxime ester compound having photobleachability contains, for example, at least one of the compound represented by the following formula (401) and the compound represented by the following formula (402). Among these, the compound represented by the formula (402) has particularly high sensitivity, and therefore is particularly likely to enhance the photocurability of the composition (X).

[0198] [ka]

[0199] [ka]

[0200] The acylphosphine oxide compound contains, for example, at least one selected from the group consisting of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)diphenylphosphine oxide.

[0201] The photoradical polymerization initiator (B1) may contain a sensitizer as a part of the photoradical polymerization initiator (B1). The sensitizer can promote the radical generation reaction of the photoradical polymerization initiator (B1) to improve the reactivity of the radical polymerization and improve the crosslink density. The sensitizer may contain at least one compound selected from the group consisting of, for example, 9,10-dibutoxyanthracene, 9-hydroxymethylanthracene, thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, anthraquinone, 1,2-dihydroxyanthraquinone, 2-ethylanthraquinone, 1,4-diethoxynaphthalene, p-dimethylaminoacetophenone, p-diethylaminoacetophenone, p-dimethylaminobenzophenone, p-diethylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, p-dimethylaminobenzaldehyde, and p-diethylaminobenzaldehyde. Note that the components that the sensitizer may contain are not limited to those mentioned above.

[0202] The content of the sensitizer in the composition (X) is, for example, 0.1 to 5 parts by mass, preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the solid content of the composition (X). When the content of the sensitizer is within such a range, the composition (X) can be cured in air, and it is not necessary to cure the composition (X) in an inert atmosphere such as a nitrogen atmosphere.

[0203] The composition (X) may contain a polymerization accelerator in addition to the photoradical polymerization initiator (B1). The polymerization accelerator contains, for example, an amine compound such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, or butoxyethyl p-dimethylaminobenzoate. Note that the components that the polymerization accelerator can contain are not limited to those mentioned above.

[0204] When the photopolymerizable compound (A) contains a cationic polymerizable compound (W), the composition (X) preferably further contains a sensitizer. In this case, the composition (X) can have particularly high cationic polymerization reactivity. The sensitizer contains, for example, either one or both of 9,10-dibutoxyanthracene and 9,10-diethoxyanthracene. The ratio of the sensitizer to the cationic polymerizable compound (W) is preferably in the range of more than 0 mass% and 1 mass% or less. In this case, the sensitizer is unlikely to inhibit the transparency of the cured product, and therefore the cured product can have good transparency.

[0205] As described above, when the photopolymerizable compound (A) contains the cationic polymerizable compound (W), the photopolymerization initiator (B) preferably contains a photocationic polymerization initiator (B2). The photocationic polymerization initiator (B2) is not particularly limited as long as it is a catalyst that generates a protonic acid or a Lewis acid upon irradiation with light. The photocationic polymerization initiator (B2) can contain at least one of an ionic photoacid generating cationic curing catalyst and a nonionic photoacid generating cationic curing catalyst.

[0206] The ionic photoacid generating cationic curing catalyst may contain at least one of onium salts and organometallic complexes. Examples of onium salts include aromatic diazonium salts, aromatic halonium salts, and aromatic sulfonium salts. Examples of organometallic complexes include iron-arene complexes, titanocene complexes, and arylsilanol-aluminum complexes. The ionic photoacid generating cationic curing catalyst may contain at least one of these components.

[0207] The nonionic photoacid generating cationic curing catalyst may contain at least one component selected from the group consisting of nitrobenzyl ester, sulfonic acid derivative, phosphoric acid ester, phenolsulfonic acid ester, diazonaphthoquinone, and N-hydroxyimide phosphonate. However, the components that the nonionic photoacid generating cationic curing catalyst may contain are not limited to the above.

[0208] More specific examples of compounds that can contain the photocationic polymerization initiator (B2) include Midori Chemical's DPI series (105, 106, 109, 201, etc.), BI-105, MPI series (103, 105, 106, 109, etc.), BBI series (101, 102, 103, 105, 106, 109, 110, 200, 210, 300, 301, etc.), and TSP series. Series (102, 103, 105, 106, 109, 200, 300, 1000, etc.), HDS-109, MDS series (103, 105, 109, 203, 205, 209, etc.), BDS-109, MNPS-109, DTS series (102, 103, 105, 200, etc.), NDS series (103, 105, 155, 165, etc.), DAM series (1 01, 102, 103, 105, 201, etc.), SI series (105, 106, etc.), PI-106, NDI series (105, 106, 109, 1001, 1004, etc.), PAI series (01, 101, 106, 1001, 1002, 1003, 1004, etc.), MBZ-101, PYR-100, NB series (101, 201, etc.), NAI series Series (100, 1002, 1003, 1004, 101, 105, 106, 109, etc.), TAZ series (100, 101, 102, 103, 104, 107, 108, 109, 110, 113, 114, 118, 122, 123, 203, 204, etc.), NBC-101, ANC-101, TPS-Acetate, DTS-Acetate, Di-Boc Bisphinol A, tert-Butyl lithocholate, tert-Butyl deoxycholate, tert-Butyl cholate, BX, BC-2, MPI-103, BDS-105, TPS-103, NAT-103, BMS-105, and TMS-105; Cyracure UVI-6970, Cyracure UVI-6974, Cyracure UVI-6990, and Cyracure UVI-950 manufactured by Union Carbide Corporation, USA; Irgacure 250, Irgacure 261 and Irgacure 264 from BASF; Ciba-Geigy CG-24-61; ADEKA OPTOMER SP-150, ADEKA OPTOMER SP-151, ADEKA OPTOMER SP-170 and ADEKA OPTOMER SP-171 manufactured by ADEKA Corporation; DAICAT II manufactured by Daicel Corporation; UVAC1590 and UVAC1591 manufactured by Daicel-Cytec Co., Ltd.; CI-2064, CI-2639, CI-2624, CI-2481, CI-2734, CI-2855, CI-2823, CI-2758, and CIT-1682 manufactured by Nippon Soda Co., Ltd.; PI-2074, tetrakis(pentafluorophenyl)borate toluylcumyl iodonium salt, from Rhodia; 3M FFC509; CD-1010, CD-1011 and CD-1012 manufactured by Sartomer, USA; CPI-100P, CPI-101A, CPI-110P, CPI-110A and CPI-210S manufactured by San-Apro Ltd.; and UVI-6992 and UVI-6976 manufactured by The Dow Chemical Company are included. The photocationic polymerization initiator (B2) may contain at least one compound selected from the group consisting of these compounds.

[0209] The ratio of the photocationic polymerization initiator (B2) to the cationic polymerizable compound (W) is preferably within the range of 1 to 4 mass%. When this ratio is 1 mass% or more, the composition (X) can have particularly good cationic polymerization reactivity. When this ratio is 4 mass% or less, the composition (X) can have good storage stability, and since it does not contain an excessive amount of the photocationic polymerization initiator (B2), it is possible to reduce the production cost.

[0210] The resin composition (X) may contain a moisture absorbent (E). The moisture absorbent (E) can impart moisture absorption to the cured product of the resin composition (X). The moisture absorbent (E) is preferably an inorganic particle having moisture absorption. The moisture absorbent (E) can contain, for example, one or more components selected from the group consisting of zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. The moisture absorbent (E) preferably contains zeolite particles, and particularly preferably contains zeolite particles having an average particle size of 200 nm or less.

[0211] The zeolite particles preferably contain sodium ions. For this purpose, the zeolite particles are preferably produced from zeolite containing sodium ions, and more preferably produced from at least one material selected from the group consisting of A-type zeolite, X-type zeolite, and Y-type zeolite among the zeolites containing sodium ions. It is particularly preferable that the zeolite particles are produced from 4A-type zeolite among the A-type zeolites. In these cases, the zeolite particles have a crystal structure suitable for adsorbing moisture.

[0212] The pH of the zeolite particles is preferably 7 or more and 10 or less. In this case, the crystals of the zeolite particles are less likely to be destroyed, and the zeolite particles are less likely to hinder the curing of the composition (X) when the composition (X) is cured. The pH of the zeolite particles is a value obtained by heating a dispersion obtained by adding 0.05 g of zeolite particles to 99.95 g of ion-exchanged water at 90° C. for 24 hours, and then measuring the pH of the supernatant of the dispersion with a pH meter. Examples of pH meter include a compact pH meter manufactured by Horiba, Ltd. <laquatwin>B-711 can be used. In order for the pH of the zeolite particles to be 7 or more and 10 or less, the zeolite particles are preferably made of FAU Y-type zeolite having protons as counter cations.

[0213] The average particle size of the moisture absorbent (E) is preferably 10 nm or more and 200 nm or less. If the average particle size is 200 nm or less, the cured product can have particularly high transparency. If the average particle size is 10 nm or more, the good moisture absorption of the moisture absorbent (E) can be maintained. The average particle size is the median diameter calculated from the measurement results by dynamic light scattering, that is, the cumulative 50% diameter (D50). As the measuring device, the Nanotrac Wave series of Microtrack Bell Co., Ltd. can be used. The average particle size of the moisture absorbent (E) is more preferably 150 nm or less, even more preferably 100 nm or less, and particularly preferably 70 nm or less. The average particle size of the moisture absorbent (E) is preferably 20 nm or more, and more preferably 50 nm or more. In this case, the cured product can have particularly good transparency and moisture absorption.

[0214] It is also preferable that the cumulative 90% diameter (D90) of the moisture absorbent (E) is 100 nm or less. In this case, the cured product can have particularly high transparency.

[0215] The proportion of the moisture absorbent (E) relative to the total amount of the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the proportion of the moisture absorbent (E) is 1% by mass or more, the cured product can have particularly high moisture absorption. If the proportion of the moisture absorbent (E) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can have a sufficiently low viscosity to be applicable by the inkjet method. The proportion of the moisture absorbent (E) is more preferably 3% by mass or more, and particularly preferably 5% by mass or more. If the proportion of the moisture absorbent (E) is 15% by mass or less, it is more preferably 13% by mass or less.

[0216] When the resin composition (X) contains the moisture absorbent (E), the resin composition (X) may contain a dispersant (G). The dispersant (G) is a surfactant that can be adsorbed to the moisture absorbent (E). The dispersant (G) has, for example, an adsorption group that can be adsorbed to the particles of the moisture absorbent (E) and a tail that is a chain-like or comb-like molecular skeleton that adheres to the particles of the moisture absorbent (E) by the adsorption group being adsorbed to the particles. The dispersant (G) can contain, for example, one or more components selected from the group consisting of an acrylic dispersant whose tail is an acrylic molecular chain, a urethane dispersant whose tail is a urethane molecular chain, and a polyester dispersant whose tail is a polyester molecular chain. The dispersant (G) can disperse the moisture absorbent (E) well in the resin composition (X) and in the cured product. This can prevent the transparency of the cured product from being reduced by the moisture absorbent (E) even if the cured product of the resin composition (X) contains the moisture absorbent (E). The dispersant (G) can also suppress the aggregation of the moisture absorbent (E) during storage of the resin composition (X). Therefore, the storage stability of the resin composition (X) can be made less likely to be reduced by the moisture absorbent (E). In addition, the adhesion between the cured product of the resin composition (X) and the inorganic material member can be prevented from being reduced by the dispersant (G). This is because the dispersant (G) is easily adsorbed to the moisture absorbent (E) and is less likely to affect the interface between the cured product and the inorganic material member. Therefore, when the resin composition (X) contains the dispersant (G), the sealant 5 can have high adhesion to the glass substrate. In addition, the adhesion between the inorganic material member and the sealant 5 can be improved. The ratio of the dispersant (G) to 100 parts by mass of the moisture absorbent (E) is preferably 5% by mass or more and 60% by mass or less. If the amount of the dispersant (G) is 5% by mass or more, the advantages of the dispersant (G) can be particularly exhibited. When the amount of the dispersant (G) is 60% by mass or less, the adhesion between the cured product of the resin composition (X) and the member made of an inorganic material can be improved.

[0217] As described above, it is preferable that the composition (X) does not contain a solvent or the content of the solvent is 1 mass% or less. Therefore, outgassing is unlikely to occur from the composition (X) and the cured product. In addition, the storage stability of the composition (X) is likely to be further improved.

[0218] Composition (X) can be prepared by mixing the above-mentioned components. Composition (X) is preferably liquid at 25°C. EXAMPLES

[0219] Specific examples of the present embodiment are presented below, but the present embodiment is not limited to the following examples.

[0220] 1. Preparation of the Composition Compositions were prepared by mixing the components shown in the following table. Details of the components shown in the table are as follows.

[0221] The viscosity of each of the following components was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The relative dielectric constant of each of the following components was measured using a dielectric constant meter (manufactured by Nippon Luft Co., Ltd., Model 871) at 25° C. and a frequency of 10 kHz. -SR506NS: Sartomer Corporation. Isobornyl acrylate. Dielectric constant: 4.7. Viscosity: 8 mPa·s. -SR423NS: Sartomer Corporation. Isobornyl methacrylate. Dielectric constant: 4.5. Viscosity: 11 mPa·s. -FA513AS: Hitachi Chemical Co., Ltd. Dicyclopentanyl acrylate. Viscosity 13 mPa·s. -FA513M: Hitachi Chemical Co., Ltd. Dicyclopentanyl methacrylate. Dielectric constant: 4.6. Viscosity: 17 mPa·s. -ADMA: Manufactured by Osaka Organic Chemical Industry Co., Ltd. Adamantyl acrylate. Dielectric constant: 4.9. Viscosity: 11 mPa·s. -MADMA: Manufactured by Osaka Organic Chemical Industry Co., Ltd. Adamantyl methacrylate. Dielectric constant: 4.9. Viscosity: 12 mPa·s -MA: Methyl acrylate. Dielectric constant: 6.1. Viscosity: 5 mPa·s. -BA: Butyl acrylate. Dielectric constant: 5.1. Viscosity: 4 mPa·s. -LA: Lauryl acrylate. Dielectric constant: 3.6. Viscosity: 4 mPa·s. -SR833S: Tricyclodecane dimethanol diacrylate. Dielectric constant: 5.6. Viscosity: 130 mPa·s. -PEGDMA: Polyethylene glycol dimethacrylate. Dielectric constant: 8.8. Viscosity: 14 mPa·s. -PEGDA: Polyethylene glycol diacrylate. Dielectric constant: 9.0. Viscosity: 20 mPa·s. -A-HD-N: 1,6 Hexanediol diacrylate. Dielectric constant: 5.8. Viscosity: 6 mPa·s. -A-NOD-N: 1,9 Nonanediol diacrylate. Dielectric constant: 5.3. Viscosity: 8 mPa·s. -A-DOD-N: 1,10 Decanediol diacrylate. Dielectric constant: 5.1. Viscosity: 9 mPa·s. -SR295NS: Pentaerythritol tetraacrylate. Dielectric constant: 11.0. Viscosity: 340mPa·s. -SR351S: Trimethylolpropane triacrylate. Dielectric constant: 8.5. Viscosity: 100mPa·s. -TAIC: Triallyl isocyanurate. Dielectric constant: 2.7. Viscosity: 100 mPa·s. -ALEOX: 3-allyloxymethyl-3-ethyloxetane. Dielectric constant: 9.5. Viscosity: 3 mPa·s. -Celloxide 8010: Daicel Corporation, (3,3',4,4'-diepoxy)bicyclohexyl. Dielectric constant: 9.1. Viscosity: 80 mPa·s. -OXT221: Toagosei Co., Ltd. 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane. Dielectric constant: 8.9. Viscosity: 10 mPa·s. -OXT212: Toagosei Co., Ltd. 2-Ethylhexyl oxetane. Dielectric constant: 7.8. Viscosity: 4 mPa·s. -TEPIC-VL: Nissan Chemical Co., Ltd. 1,3,5-tris(4,5-epoxypentyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione. Dielectric constant: 4.7. Viscosity: 7000mPa·s. -CHDVE: 1,4-Cyclohexanedimethanol divinyl ether. Dielectric constant: 6.2. Viscosity: 4.5 mPa·s. -DEGDVE: Diethylene glycol divinyl ether. Dielectric constant 7.2. Viscosity 2mPa·s. -TEGDVE: Triethylene glycol divinyl ether. Dielectric constant: 7.9. Viscosity: 4 mPa·s. -184: Manufactured by BASF. Product name: Irgacure 184. 1-Hydroxy-cyclohexyl-phenyl-ketone. -TPO: BASF. Product name: Irgacure TPO. 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. -DTS-200: Manufactured by Midori Chemical. Part number DTS-200. C6H5-S-C6H4-S+(C6H5)2·B(C6F5)4.

[0222] 2.Evaluation Test The following evaluation tests were carried out on the examples and comparative examples, and the results are shown in the table below.

[0223] (1) Viscosity The viscosity of the composition was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The measurements were performed under the following conditions.

[0224] (2) Glass transition temperature of the cured product The composition was applied to prepare a coating film, and the coating film was then irradiated with 100 mW / cm 2 UV light using a UV irradiator (manufactured by Ushio Inc., model number E075IIHD, peak wavelength 395 nm) in an air atmosphere. 2 A film with a thickness of 100 μm was produced by photocuring the resin under the above conditions.

[0225] The glass transition temperature of the film obtained above was measured using a viscoelasticity spectrometer "DMS6100" manufactured by Seiko Instruments Inc. Dynamic viscoelasticity measurement (DMA) was performed with a tensile module at a frequency of 10 Hz, and the temperature at which tan δ was maximized when the temperature was raised from room temperature to 200°C at a heating rate of 5°C / min was determined as the glass transition temperature.

[0226] (3) Inkjet compatibility The composition was placed in a cartridge of an inkjet printer (manufactured by Ricoh Co., Ltd., model number MH2420), and it was confirmed that the composition in the cartridge could be ejected from the nozzle of the inkjet printer.

[0227] A silicon nitride film was prepared on a glass plate as a substrate by plasma CVD, and the silicon nitride film was subjected to oxygen plasma treatment. Next, a composition was ejected from the nozzle of an inkjet printer toward the silicon nitride film to continuously print test patterns. The composition coating was visually observed and rated as follows: "A" if the coating was smooth, "B" if unevenness was observed in part of the coating, and "C" if unevenness was observed throughout the coating. It can be judged that the less unevenness there is in the coating, the less disturbance in the trajectory of the droplets of the composition ejected from the nozzle.

[0228] (4) Dielectric constant of the composition The relative dielectric constant of the composition was measured using a dielectric constant meter (Nihon Luft Co., Ltd., Model No. MODEL871) at a temperature of 25° C. and a frequency of 10 kHz.

[0229] (5) Dielectric constant of the cured product The composition was applied onto an aluminum substrate having dimensions of 80 mm × 40 mm × 1 mmt to prepare a coating film having a thickness of 10 μm. This coating film was irradiated with 100 mW / cm 2 UV light using a UV irradiator (manufactured by Ushio Inc., model number E075IIHD, peak wavelength 395 nm) in an air atmosphere. 2 The film was prepared by photocuring the film under the conditions of 15 seconds of ultraviolet irradiation ...

[0230] [Table 1] [Explanation of symbols]

[0231] 1 Light emitting device 10 Touch Sensor 100 Touch Panel< / laquatwin>

Claims

1. Contains a photopolymerizable compound (A) and a photopolymerization initiator (B), the photopolymerizable compound (A) has a relative dielectric constant of 8.0 or less at 25° C. and a frequency of 10 kHz and a viscosity of 50 mPa s or less at 25° C.; Molded by an inkjet method (excluding the case where a coagulable gas is contained and the case where the photopolymerizable compound (A) is only 1,6-hexanediol diacrylate), UV curable resin composition.

2. The photopolymerizable compound (A) contains at least one of a radical polymerizable compound and a cationic polymerizable compound. The ultraviolet-curable resin composition according to claim 1 .

3. The photopolymerizable compound (A) contains at least one compound selected from the group consisting of isobornyl acrylate, isobornyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, adamantyl acrylate, adamantyl methacrylate, methyl acrylate, butyl acrylate, lauryl acrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, 1,6 hexanediol diacrylate, 1,9 nonanediol diacrylate, 1,10 decanediol diacrylate, 3-allyloxymethyl-3-ethyloxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 2-ethylhexyloxetane, 1,4-cyclohexanedimethanol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether. The ultraviolet-curable resin composition according to claim 1 or 2.

4. The photopolymerizable compound (A) contains a component (P) consisting of at least one compound having a relative dielectric constant of 7.0 or less at 25° C. and a frequency of 10 kHz and a viscosity of 50 mPa s or less at 25° C., The ratio of the component (P) to the photopolymerizable compound (A) is 50 mass% or more. The ultraviolet-curable resin composition according to claim 1 .

5. The component (P) contains at least one compound selected from the group consisting of isobornyl acrylate, isobornyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, adamantyl acrylate, adamantyl methacrylate, methyl acrylate, butyl acrylate, lauryl acrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, and 1,4-cyclohexanedimethanol divinyl ether. The ultraviolet-curable resin composition according to claim 4.

6. a ratio of a compound having a relative dielectric constant of more than 7.0 at 25° C. and a frequency of 10 kHz in the photopolymerizable compound (A) is 0% by mass or more and 13% by mass or less with respect to the photopolymerizable compound (A); The ultraviolet-curable resin composition according to claim 1 .

7. At least one of the viscosity at 25°C and the viscosity at 40°C is 40 mPa·s or less; The ultraviolet-curable resin composition according to claim 1 .

8. Contains no solvent or has a solvent content of 1% by mass or less; The ultraviolet-curable resin composition according to claim 1 .

9. To produce an optical component that transmits light emitted by a light source, The ultraviolet-curable resin composition according to claim 1 .

10. A method for manufacturing a light emitting device including a light source and an optical component that transmits light emitted by the light source, comprising the steps of: The ultraviolet-curable resin composition according to any one of claims 1 to 9 is molded by an inkjet method to prepare a coating film; and producing the optical component by irradiating the coating with ultraviolet light. A method for manufacturing a light emitting device.

11. A light source and an optical component that transmits light emitted by the light source, the optical component being made of a cured product of the ultraviolet-curable resin composition according to any one of claims 1 to 9. Light emitting device.

12. A light-emitting device comprising: the light-emitting device according to claim 11; and a touch sensor. Touch panel.

Citation Information

Patent Citations

  • Sealant for organic electroluminescent display element

    JP2017228414A

  • Ultraviolet ray-curable resin composition, method for manufacturing organic el light-emitting device and organic el light-emitting device

    JP2018111792A

  • Method for manufacturing porous body, porous body, method for manufacturing device, device, method for manufacturing wiring structure, and wiring structure

    WO2016052473A1

  • Ink composition and organic electroluminescent element using same

    WO2018051732A1

  • Sealant for organic electroluminescent display element

    WO2018074506A1